Age differences in autobiographical memory across the adult lifespan: older adults report stronger phenomenology. Issue 1 (2nd January 2018) - Luchetti, Martina; Sutin, Angelina R.
ABSTRACT: As an individual's life story evolves across adulthood, the subjective experience (phenomenology) of autobiographical memory likely changes. In addition to age at retrieval, both the recency of the memory and the age when a memory is formed may be particularly important to its phenomenology. The present work examines the effect of three temporal factors on phenomenology ratings: (a) age of the participant, (b) age at the event reported in the memory, and (c) memory age (recency). A large sample of Americans ( N  = 1120), stratified by chronological age, recalled and rated two meaningful memories, a Turning Point and an Early Childhood Memory. Ratings of phenomenology (e.g., vividness of turning points) were higher among older adults compared to younger adults. Memories of events from the reminiscence bump were more positive in valence than events from other time periods but did not differ on other phenomenological dimensions; recent memories had stronger phenomenology than remote memories. In contrast to phenomenology, narrative content was generally unrelated to participant age, age at the event, or memory age. Overall, the findings indicate age-related differences in how meaningful memories are re-experienced.